Career Education: What It Is Not And What It Might Be - Sankey, Gerald R. (Canadian Journal of Counselling and Psychotherapy, 2012)
The sudden popularity of career education may prove to be its own worst enemy, for almost everyone will try to use it for his own ends. The key question may be, what is not career education and how may it be prevented from masquerading as the real thing. With this in mind, several current approaches which have at times been labelled career education are examined and found to be somewhat atheoretical and inconsistent with accepted definitions of career education. In an attempt to clarify this situation some general notions derived from career development theory are examined. Finally the implications of these notions for practicing counsellors are discussed.